Experimental exposure to low concentrations of Neoparamoeba perurans induces amoebic gill disease in Atlantic salmon - Bridle, AR; Hill, T; Smith, A; Crosbie, P; Nowak, BF (Journal of Fish Diseases, 2021)
Amoebic gill disease (AGD) is a significant issue in Atlantic salmon mariculture. Research on the development of treatments or vaccines uses experimental challenges where salmon is exposed to amoebae concentrations ranging from 500 to 5,000/L. However, the water concentrations of N.perurans on affected salmon farms are much lower. The lowest concentration of N.perurans previously reported to cause AGD was 10/L. Here, we report that concentrations as low as 0.1/L of N.perurans can cause AGD. We propose that concentrations of N.perurans that reflect those measured on salmon farms should be used for future experimental challenges.